Listening effort and fatigue among cochlear implant users: a scoping review - Cato Philips; Cato Philips; Laure Jacquemin; Laure Jacquemin; Marc J. W. Lammers; Marc J. W. Lammers; Griet Mertens; Griet Mertens; Annick Gilles; Annick Gilles; Annick Gilles; Olivier M. Vanderveken; et al. (Frontiers in Neurology, 2023)
IntroductionIn challenging listening situations, speech perception with a cochlear implant (CI) remains demanding and requires high levels of listening effort, which can lead to increased levels of listening-related fatigue. The body of literature on these topics increases as the number of CI users rises. This scoping review aims to provide an overview of the existing literature on listening effort, fatigue, and listening-related fatigue among CI users and the measurement techniques to evaluate them.MethodsThe Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statements were used to conduct the scoping review. The search was performed on PubMed, Scopus, and Web of Science to identify all relevant studies.ResultsIn total, 24 studies were included and suggests that CI users experience higher levels of listening effort when compared to normal hearing controls using scales, questionnaires and electroencephalogram measurements. However, executing dual-task paradigms did not reveal any difference in listening effort between both groups. Uncertainty exists regarding the difference in listening effort between unilateral, bilateral, and bimodal CI users with bilateral hearing loss due to ambiguous results. Only five studies were eligible for the research on fatigue and listening-related fatigue. Additionally, studies using objective measurement methods were lacking.DiscussionThis scoping review highlights the necessity for additional research on these topics. Moreover, there is a need for guidelines on how listening effort, fatigue, and listening-related fatigue should be measured to allow for study results that are comparable and support optimal rehabilitation strategies.